CHEMOPREVENTIVE EFFECTS OF CYCLOOXYGENASE-2 INHIBITORS AGAINST 1,2-DIMETHYL HYDRAZINE (DMH)INDUCED RAT COLON CARCINOGENESIS - Gungor, Hilal; Ilhan, Nevin; Eroksuz, Hatice; Ozercan, Ibrahim H. (Int Inst Anticancer Research, 2014)
[Abstract Not Available]